2017
DOI: 10.1038/leu.2017.121
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-outcome correlations in pediatric AML: the impact of a monosomal karyotype in trial AML-BFM 2004

Abstract: We conducted a cytogenetic analysis of 642 children with de novo acute myeloid leukemia (AML) treated on the AML-Berlin-Frankfurt-Münster (BFM) 04 protocol to determine the prognostic value of specific chromosomal aberrations including monosomal (MK+), complex (CK+) and hypodiploid (HK+) karyotypes, individually and in combination. Multivariate regression analysis identified in particular MK+ (n=22) as a new independent risk factor for poor event-free survival (EFS 23±9% vs 53±2% for all other patients, P=0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 47 publications
4
20
2
Order By: Relevance
“…Our study distinguishes MK as an independent predictor of inferior EFS but, in contrast to the findings by Rasche et al (), the high proportion of events did not translate into a poor OS. This discrepancy may be explained by the fact that the comparison group of the current study did not include patients with CBF abnormalities who, according to previous reports, fare exceedingly well after relapse (Kaspers et al , ; Karlsson et al , ).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study distinguishes MK as an independent predictor of inferior EFS but, in contrast to the findings by Rasche et al (), the high proportion of events did not translate into a poor OS. This discrepancy may be explained by the fact that the comparison group of the current study did not include patients with CBF abnormalities who, according to previous reports, fare exceedingly well after relapse (Kaspers et al , ; Karlsson et al , ).…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with previous findings in adult AML populations (Grimwade et al, 1998;Slovak et al, 2000;Byrd et al, 2002;Haferlach et al, 2012), CK predicted an adverse prognosis in the present study and showed inferior EFS and OS compared to non-CK patients. The poor EFS associated with CK was mitigated by the omission of patients with MK and corresponds to the observations in the recent report from the AML-Berlin-Frankf€ urt-Muenster (BFM) 2004 trial (Rasche et al, 2017). Taken together, our data suggest that, in patients with multiple non-recurrent chromosomal abnormalities, the event of chromosome loss in particular heralds an increased risk of early events, such as primary refractoriness to chemotherapy.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Risk stratification in pediatric AML has previously been based on the presence of a handful of genetic features and responses to therapy. Those with favorable genetics include t(8;21), inv(16), NPM1 mutations, and CEBPA mutations, each of which carries EFS and OS rates of approximately 65–70% and 80%, respectively [ 1 , 4 , 11 ]. t(8;21) and inv(16), collectively termed core binding factor (CBF) AML, represent the most common cytogenetic subgroup in pediatric AML accounting for 20–25% of cases [ 1 , 10 ••, 11 ].…”
Section: Geneticsmentioning
confidence: 99%